Therapeutic outcomes of laryngeal closure and laryngostomy in children with recurrent pneumonia. (September 2022) - Murakami, Daizo; Miyamaru, Satoru; Nishimoto, Kohei; Ise, Momoko; Samejima, Yasuhiro; Ozasa, Shiro; Nakamura, Kimitoshi; Orita, Yorihisa
Abstract: Purpose: Children with medical complexity frequently experience difficulty breathing and swallowing and occasionally develop aspiration pneumonia. Long-term intubation may cause fatal trachea-innominate artery fistula (TIF). In the present study, we retrospectively evaluated the efficacy of laryngeal closure and laryngostomy in children with medical complexity. Materials and methods: Laryngeal closure and laryngostomy were performed in eight children with severe neuromuscular disorders who were incapable of oral ingestion and verbal communication. The laryngostoma was placed at a higher position compared to that in conventional tracheostomies for easier management of the airway and to prevent TIF. Results: Aspiration was successfully prevented postoperatively in all cases. Laryngocutaneous fistula formation was not observed. Two patients successfully achieved oral ingestion capability and tracheal cannulas were removed in two patients. Among the six patients who needed a mechanical ventilator before surgery, two patients were weaned from mechanical ventilation. Five patients were successfully discharged from the hospital. Although two patients died because of their primary condition, pneumonia exacerbation was not observed in any of the patients. Conclusion: Compared to the conventional tracheostomy, our procedure improved airway management and function in children with medical complexity and reduced the risk of TIF.